2013
DOI: 10.17305/bjbms.2013.2332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-dose neuropeptide Y on levels of hippocampal BDNF, MDA, GSH, and NO in a rat model of pentylenetetrazole-induced epileptic seizure

Abstract: Epilepsy is one of the most common neurological disorders, characterized by recurrent seizures, which may increase the content of reactive oxygen and nitrogen species. Th e objective of this study was to investigate the eff ects of Neuropeptide Y on oxidative and nitrosative balance and brain-derived neurotrophic factor levels induced by pentylenetetrazole (a standard convulsant drug) in the hippocampus of Wistar rats. Th ree groups of seven rats were treated intraperitoneally as follows: group  (saline + sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…However, there was no significant but considerable decrease in the level of BDNF in NPY-treated rats (285.8 ± 53.6 ng g −1 protein) in comparison to untreated rats of the group (ii) 377.9 ± 27.5 ng g −1 protein. All these data support the neuroprotective property of NPY [93] Galantamine is an alkaloid compound that acts as an acetylcholinesterase inhibitor and allosteric potentiator of nicotinic receptors. It has been investigated for its potential antiepileptic effects [94].…”
Section: Role Of Neuropeptide Y In Epilepsysupporting
confidence: 64%
“…However, there was no significant but considerable decrease in the level of BDNF in NPY-treated rats (285.8 ± 53.6 ng g −1 protein) in comparison to untreated rats of the group (ii) 377.9 ± 27.5 ng g −1 protein. All these data support the neuroprotective property of NPY [93] Galantamine is an alkaloid compound that acts as an acetylcholinesterase inhibitor and allosteric potentiator of nicotinic receptors. It has been investigated for its potential antiepileptic effects [94].…”
Section: Role Of Neuropeptide Y In Epilepsysupporting
confidence: 64%
“…Besides, MDA is involved in the production of oxygen free radicals (OFRs) that injure cellular membranes while those of SOD and GSH‐Px generated in cells and tissues of animals under the changing pathological conditions by acting as scavengers of OFRs . A previous study found that a single‐dose treatment with neuropeptide Y decreased the MDA level and enhanced GSH levels in rats with pentylenetetrazole‐induced epileptic seizures . Furthermore, astrocytes at neural synapses contribute to synaptogenesis through normally exhibiting increased apolipoprotein E expression and GFAP reactivity in neurodegenerative disease states .…”
Section: Discussionmentioning
confidence: 97%
“…44 A previous study found that a single-dose treatment with neuropeptide Y decreased the MDA level and enhanced GSH levels in rats with pentylenetetrazoleinduced epileptic seizures. 45 Furthermore, astrocytes at neural synapses contribute to synaptogenesis through normally exhibiting increased apolipoprotein E expression and GFAP reactivity in neurodegenerative disease states. 46 It can be explained by that when PC12 cells induced with the heat stress, GFAP levels were decreased, while PC12 cells, which are overexpressed in the gene encoding GFAP, showed resistance.…”
Section: Discussionmentioning
confidence: 99%
“…NPY can stimulate autophagy in mouse and rat hypothalamic neural cells by activating Y1R and Y5R [ 79 ]. Additionally, an A1-40 mouse model treated with exogenous NPY demonstrated reduced oxidative stress, and mitochondrial dysfunction, via blockade of NO production and reduced lipid peroxidation [ 80 , 81 ].…”
Section: Npy and The Nutritional Microenvironmentmentioning
confidence: 99%